Adubação com potássio e cálcio na nutrição e produção de goiabeira 'Paluma' - Cavalcante, Alian Cássio Pereira; Cavalcante, Lourival Ferreira; Bertino, Antonio Michael Pereira; Cavalcante, Adailza Guilherme; Lima Neto, Antonio João De; Ferreira, Nubia Marisa (Universidade Federal de Viçosa, 2019)
ABSTRACT The guava is a fruit cultivated worldwide, distinguished by the great acceptance in the consumer market. However, so that the crop exploits its maximum productive potential and maintains the quality of the fruits it is necessary an adequate mineral fertilization to raise the availability of nutrients in the soil and to increase the absorption by plants. The objective of the work was to evaluate the effects of fertilization with potassium doses, in the presence and absence of calcium, on the nutritional status and on the production of 'Paluma' guava. The experiment was carried out from August 2015 to May 2016, in the municipality of Remígio-PB, Brazil. The variables analyzed were: macro and micronutrient leaf contents, number of fruits per plant, average fruit mass, fruit yield per plant and productivity. Guava plants were adequately supplied with nitrogen, phosphorus, potassium, calcium, magnesium, boron, iron and manganese, and deficient in sulfur, copper and zinc. Calcium fertilization increased the leaf content of P, K, Ca, S, B, Mn and Zn, but reduced the number of fruits per plant and the yield of 'Paluma' guava. Potassium fertilization without calcium addition at doses between 101 and 143 g plant-1 year-1 K2O at 16 months of age provides the highest productivity of 'Paluma' guava.

RESUMO A goiabeira é uma frutífera cultivada mundialmente, destacando-se pela grande aceitação no mercado consumidor. Entretanto, para que a cultura explore o seu máximo potencial produtivo e mantenha a qualidade dos frutos, é necessária a adequada adubação mineral para elevar a disponibilidade de nutrientes no solo e aumentar sua absorção pelas plantas. Objetivou-se, com este trabalho, avaliar os efeitos da adubação com doses de potássio, na presença e na ausência de cálcio, no estado nutricional e na produção da goiabeira 'Paluma'. O experimento foi desenvolvido de agosto de 2015 a maio de 2016, no município de Remígio, Paraíba. As variáveis analisadas foram: teores foliares de macro e de micronutrientes, número de frutos por planta, massa média de frutos, produção de frutos por planta e produtividade. As plantas da goiabeira estavam adequadamente supridas em nitrogênio, fósforo, potássio, cálcio, magnésio, boro, ferro, manganês e deficientes em enxofre, cobre e zinco. A adubação com cálcio incrementou os teores foliares de P, K, Ca, S, B, Mn e Zn e reduziu o número de frutos por planta e a produtividade da goiabeira 'Paluma'. A adubação potássica sem adição de cálcio, nas doses entre 101 e 143 g planta-1 ano-1 de K2O, aos 16 meses de idade, proporcionou a maior produtividade da goiabeira 'Paluma'.
Fertilization with potassium and calcium in nutrition and production of guava 'Paluma'
Keywords: Psidium guajava L.; fertilizing; nutrition; productivity.; Psidium guajava L.; adubação; nutrição; produtividade.